Application of phyllosphere bacterial antagonist against rice sheath blight - Akter, Shamima (2015)
Antagonistic bacteria originating from the rhizosphere are being used in sheath blight management. However, little is known about the potential of bacteria inhabiting the phyllosphere. Hence, a study was initiated with the aim of assessing the effective bacterial antagonists against the disease. A total of 325 bacterial isolates obtained from 100 rice plant samples collected from different locations of Malaysia and Bangladesh were preliminarily screened. Out of the 325 bacterial isolates, 14 were selected based on their ability to inhibit the growth of R. solani. In dual culture tests isolates KMB25, TMB33, PMB38, UMB20 and BMB42 showed 68.44, 60.89, 60.22, 50.00 and 48.22% inhibitions, respectively. In extracellular metabolites tests most of these isolates showed comparatively higher percentages of growth inhibition of the fungus than in dual culture tests. Selected isolates were negative to indole, methyl red, Voges Proskaeur, and starch hydrolysis but positive to catalase, urease, and nitrate reduction tests. Isolates KMB25, TMB33 and PMB38 were positive to gelatin liquefaction, while isolates UMB20 and BMB42 were negative to the test. Biolog identified P. fluorescens (UMB20), P. aeruginosa (KMB25, TMB33 and PMB38) and P. asplenii (BMB42) with the similarity index ranging from 0.52 to 0.70. The identities of the selected three bacterial isolates UMB20, KMB25 and BMB42 were further confirmed through 16S rDNA gene sequencing. According to the GenBank database of NCBL, UMB20 and BMB42 were identified as P. fluorescens and KMB25 as P. aeruginosa. Fungal growth inhibition ranging from 86.85 to 93.15% was obtained by these strains in volatile and 100% was in diffusible metabolites test. Among the 3 strains, UMB20 and BMB42 produced indole 3-acetic acid and chitinase, but not protease. All of them produced cellulase, siderophore, HCN, and ammonia and were able to solubilize phosphate. Strains UMB20 and BMB42 were preserved in peat and talc as single strains or in mixtures. The peat formulation was found to be more suitable than talc to retain longer shelf life of individuals and strain mixtures with sufficient viable cells. At 4°C of storage condition peat formulations were better than room temperature (28±2°C) condition. In bioefficacy tests of peat based bacterial formulations under glass house conditions, the strain mixture and UMB20 alone significantly reduced the disease severity in terms of area under disease progress curve (AUDPC) compared to the untreated control. Percent reduction of AUDPC was 32.79, 32.58 and 21.19 for strain mixture (UMB20+BMB42), UMB20 and BMB42, respectively. Significantly lowest disease progression rate (0.01unit/day) was found in the strain mixture applied plants. In addition to disease suppression, the strain mixture enhanced the plant height, percentage of effective tillers per hill, and percentage of fertile spikelets per panicle. Effects of all the treatments on flag leaf area, total number of tillers and number of effective tillers were insignificant. Significantly highest weight of 100-grain (1.65 g) was obtained from the strain mixture applied plants. The Pseudomonas bacteria isolated from rice plants had the potential to inhibit the fungal growth in vitro and in vivo and possessed most of the plant growth promoting characteristics. They have the potential to be utilized as biocontrol agents for management of sheath blight in rice.